2017
DOI: 10.1186/s12966-017-0612-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and calorie intake mediate the relationship from depression to body fat mass among female Mexican health workers

Abstract: BackgroundDepression is a foremost cause of morbidity throughout the world and the prevalence of depression in women is about twice as high as men. Additionally, overweight and obesity are major global health concerns. We explored the relationship between depression and body fat, and the role of physical activity and diet as mediators of this relationship in a sample of 456 adult female Mexican health workers.MethodLongitudinal and cross-sectional analyses using data from adult women of the Health Workers Coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…A cross-sectional study using data from National Health and Nutrition Examination Surveys in the United States showed that physical activity mediated 79% of the effect of MDD on BMI in young adults, but diet quality was not involved in this association 28 . A longitudinal study carried out with female Mexican health workers, exploring the bidirectional association between depression and body fat, showed that higher caloric intake and lower physical activity in leisure time mediated the effect of depressive symptoms on body fat, and no effects of obesity on depression were found 29 . In our data, obesity was associated with higher physical activity, contrary to what would be expected, which could explain the lack of an indirect effect by this variable.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study using data from National Health and Nutrition Examination Surveys in the United States showed that physical activity mediated 79% of the effect of MDD on BMI in young adults, but diet quality was not involved in this association 28 . A longitudinal study carried out with female Mexican health workers, exploring the bidirectional association between depression and body fat, showed that higher caloric intake and lower physical activity in leisure time mediated the effect of depressive symptoms on body fat, and no effects of obesity on depression were found 29 . In our data, obesity was associated with higher physical activity, contrary to what would be expected, which could explain the lack of an indirect effect by this variable.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity intervention plays a part in weight loss which happens to be an alternative for the prevention and treatment of the depression symptoms [ 76 ]. Moreover, poor sleep incite less motivation to do exercise that leads to weight gain and also obesity-related problemsas well as sleep disturbances [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, poor sleep incite less motivation to do exercise that leads to weight gain and also obesity-related problemsas well as sleep disturbances [ 77 ]. Promotingphysical activity in an individual’s lifestyle can also benefit in averting the potentialenhancement of chronic diseases for which body weight is a risk factor [ 76 ]. Consistent with previous literature [ 78 ], excessive weight gain probably happen alliance with low physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety appeared to lead to unhealthy lifestyles in rising studies, included physical inactivity, unhealthy diet, smoking habits (23), higher calorie intake, and body fat (24). Studies indicated that lifestyle changes had the potential to reduce the risk or symptoms of depression and anxiety (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that hypertensive patients with anxiety or depression may display increased healthcare utilization (21) and the treatment of depression or anxiety disorders in individuals with hypertension may help improve medication adherence rates and healthcare outcomes (22). Depression and anxiety appeared to lead to unhealthy lifestyles in rising studies, included physical inactivity, unhealthy diet, smoking habits (23), higher calorie intake, and body fat (24). Studies indicated that lifestyle changes had the potential to reduce the risk or symptoms of depression and anxiety (25,26).…”
Section: Introductionmentioning
confidence: 99%